Influence of gestational and perinatal factors on body composition of full-term newborns - Sylvia Reis Gonçalves Nehab; Letícia D. Villela; Andrea D. Abranches; Daniele M. Rocha; Leila M.L. da Silva; Yasmin N.V. Amaral; Saint Clair G. Junior; Fernanda V.M. Soares; Maria Dalva Barborsa Beker Méio; Maria Elisabeth L. Moreira (Elsevier, 2020)
Objective: To evaluate the influence of gestational and perinatal factors on body composition and birth weight of full-term newborns. Method: This was a cross-sectional study, within a prospective cohort, consisting of 124 postpartum women and their newborns. Data included the following: maternal age; ethnicity; pre-gestational body mass index; gestational weight gain; parity; gestational morbidities (hypertension and gestational diabetes mellitus); gestational age at birth; birth weight; and newborn's gender. Anthropometric and body composition data of the newborns were collected using air-displacement plethysmography (PeaPod® Infant Body Composition System-LMI; Concord, CA, USA). The stepwise technique was applied to a multiple linear regression model. Results: The significant variables in the model that explained 84% of the variation in neonatal fat-free mass were: birth weight; maternal age; newborn's gender and gestational age. For body fat mass: birth weight; newborn's gender; gestational arterial hypertension; gestational diabetes; and gestational weight gain. These variables explained 60% and 46% of fat mass, in grams and as a percentage, respectively. Regarding birth weight, the significant factors were gestational age, pre-gestational BMI, and gestational weight gain. Female newborns showed higher body fat mass and male newborns had higher fat-free mass. Conclusion: Gestational and perinatal factors influence neonatal body composition. Early identification of these gestational factors, which may be modifiable, is necessary to prevent obesity and chronic noncommunicable diseases in the future. Resumo: Objetivo: Avaliar a influência de fatores gestacionais e perinatais na composição corporal e no peso de nascimento de recém-nascidos a termo. Método: Estudo transversal, dentro de uma coorte prospectiva, composto por 124 puérperas e seus recém-nascidos. Os dados incluíram: idade materna; etnia; índice de massa corpórea pré-gestacional; ganho de peso gestacional; paridade; morbidades gestacionais, (hipertensão arterial e diabetes mellitus gestacional); idade gestacional do nascimento; peso de nascimento; e sexo do recém-nascido. Os dados antropométricos e de composição corporal dos recém-nascidos, foram coletados com a pletismografia por deslocamento de ar (PeaPod®). Foi aplicada a técnica de stepwise no modelo de regressão linear múltipla. Resultados: As variáveis significativas do modelo que explicou 84% da variação da massa livre de gordura neonatal foram: peso de nascimento; idade materna; sexo do recém-nascido; e idade gestacional. Para a massa de gordura corporal: peso de nascimento; sexo do recém-nascido; hipertensão arterial gestacional; diabetes gestacional; e ganho de peso gestacional. Essas variáveis explicaram 60% e 46% da massa de gordura, em gramas e percentual, respectivamente. Em relação ao peso de nascimento os fatores significativos foram: idade gestacional; IMC pré-gestacional; e ganho de peso gestacional. Os recém-nascidos do sexo feminino apresentaram maior massa de gordura corporal e os do sexo masculino maior massa livre de gordura. Conclusão: Fatores gestacionais e perinatais influenciam a composição corporal neonatal. A identificação precoce desses fatores gestacionais, que podem ser modificáveis, é necessária para prevenção de obesidade e de doenças crônicas não transmissíveis no futuro.